PENGGUNAAN METODE FUZZY TSUKAMOTO PADA PENERIMAAN JURNAL DI SUATU INSTITUSI - Saputro, Bayu Dwi; Pratama, Rafli (JURNAL TEKNIK INFORMATIKA UNIS, 2021)
Journal acceptance is a difficult problem to solve because in its implementation it involves several reviewers who can produce different decisions from various perspectives. Therefore, a decision support system is needed to assist reviewers in deciding whether to accept papers. This study aims to develop a decision support system using the Fuzzy Tsukamoto method for journal acceptance. The Fuzzy Tsukamoto method describes the relationship between the input and output of the system by using a set of fuzzy if-then rules. From the comparison results, the accuracy of the comparison of manual methods, expert decisions, and journal acceptance DSS using the Fuzzy Tsukamoto method is 95% with an error of 5%. Based on the results of accuracy and error, it shows that the DSS journal acceptance using the Fuzzy Tsukamoto method is accurate and has high precision.